2022
DOI: 10.1111/evo.14613
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary consequences of pesticide exposure include transgenerational plasticity and potential terminal investment transgenerational effects

Abstract: Transgenerational plasticity, the influence of the environment experienced by parents on the phenotype and fitness of subsequent generations, is being increasingly recognized. Human-altered environments, such as those resulting from the increasing use of pesticides, may be major drivers of such cross-generational influences, which in turn may have profound evolutionary and ecological repercussions. Most of these consequences are, however, unknown. Whether transgenerational plasticity elicited by pesticide expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 95 publications
(189 reference statements)
0
1
0
Order By: Relevance
“…Our results show that there are important and far-reaching transgenerational effects of non-lethal pesticide exposure, as we detected an increase in the longevity of grandsons whose grandparent was exposed, regardless of their sex. These results are consistent with Castano-Sanz et al [38], who showed that grand-offspring lived longer after parental exposure to deltamethrin. Extended longevity implies higher chances for additional matings, and consequently an increased number of descendants.…”
Section: (C) Transgenerational Effectssupporting
confidence: 92%
See 3 more Smart Citations
“…Our results show that there are important and far-reaching transgenerational effects of non-lethal pesticide exposure, as we detected an increase in the longevity of grandsons whose grandparent was exposed, regardless of their sex. These results are consistent with Castano-Sanz et al [38], who showed that grand-offspring lived longer after parental exposure to deltamethrin. Extended longevity implies higher chances for additional matings, and consequently an increased number of descendants.…”
Section: (C) Transgenerational Effectssupporting
confidence: 92%
“…These C. maculatus selection lines were raised under either enforced monogamy or unrestricted polygamy for over 84 generations, therefore, imposing relaxed versus strong sexual selection, respectively [43,44]. In a previous study, we confirmed that non-lethal concentrations of the pesticide deltamethrin trigger transgenerational effects in a population of C. maculatus [38]. Here, we exposed males and females from the experimentally evolved lines differing in the strength of sexual selection to the pesticide, hence testing the role of past sexual selection in shaping stress-induced transgenerational effects (figure 1).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Nonetheless, most ectothermic females reach adulthood at a smaller size under high temperatures (Angilletta Jr, 2009 ; Atkinson, 1994 ), but there are also exceptions to this temperature–size rule (Fu et al., 2016 ; Kingsolver et al., 2007 ; Walters & Hassall, 2006 ; Walzer et al., 2020 ). Third, in species with sexually dimorphic egg sizes, heat‐stressed females may also invest energy depending on offspring sex, as documented in predatory mites exposed to food stress (Walzer & Schausberger, 2015 ) and seed beetles exposed to pesticides (Castano‐Sanz et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%